LIVING QUR’AN DALAM TRADISI PEMBACAAN SURAH AL-INSHIRĀH DI LEMBAGA TAMAN PENDIDIKAN IHYAUL ULUM CANGAAN GRESIK - Kurnia Wahidah; Ahmad Saddad (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2024)
This research examines the tradition of reciting Surah Al-Inshirāh at the Ihyaul Ulum Education Park Institution in Cangaan, Gresik Regency, from the perspective of Living Qur'an. The study aims to reveal the "because" and "in order" motives of this tradition using Alfred Schutz's phenomenological approach. Data was collected through observation, interviews, and documentation. The findings indicate that the "because motive," or the reason motive, includes remembering Allah SWT, obtaining rewards, following OSIS regulations, and knowing the virtues of Surah Al-Inshirāh. Meanwhile, the "in order motive," or the purpose motive, includes istiqomah (consistency), a calmer heart, obtaining the virtues of the surah, increasing faith in Allah, and facilitating memorization and preventing forgetfulness. The tradition of reciting Surah Al-Inshirāh has the potential to be applied in other Islamic educational institutions, with the impact of increasing student spirituality, which can be adapted through integration into daily activities and providing understanding of its meaning and virtues. Penelitian ini mengkaji tradisi pembacaan Surah Al-Inshirāh di Lembaga Taman Pendidikan Ihyaul Ulum Cangaan Kabupaten Gresik dalam perspektif Living Qur'an. Penelitian bertujuan untuk mengungkap motif "because" dan "in order" dari tradisi ini menggunakan pendekatan fenomenologi Alfred Schutz. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi. Temuan menunjukkan bahwa Because motive, atau motif sebab, meliputi mengingat Allah Swt., mendapatkan pahala, mengikuti peraturan OSIS, dan mengetahui fadilah dari Surah Al-Inshirāh. Sementara itu, in order motive, atau motif tujuan, mencakup istiqomah, hati menjadi lebih tenang, mendapatkan faḍīlah dari surah tersebut, meningkatkan iman kepada Allah, serta memudahkan dalam menghafal dan tidak mudah lupa. Tradisi pembacaan Surah Al-Inshirāh memiliki potensi untuk diterapkan di lembaga pendidikan Islam lainnya, dengan dampak peningkatan spiritualitas siswa yang dapat diadaptasi melalui integrasi dalam kegiatan harian dan pemberian pemahaman tentang makna serta fadhilahnya.